Компьютерная обработка текстов в качественных и количественных социологических исследованиях - Горбачик, А. (Социология: теория, методы, маркетинг, 2006)
The author substantiates the necessity of computerized work with texts in qualitative and quantitative empirical sociological studies. Based on the analysis of opportunities provided by known software for work with texts the author offers a procedure with text data in quantitative and mixed (containing both qualitative and quantitative) empirical research. Besides, he suggests the program realization of this procedure as an extension to the statistical analysis package named as a Sociological Questionnaire Handling (SQH).